A REALIDADE AUMENTADA COMO UMA CONTRIBUIÇÃO PARA O ENSINO DE SÓLIDOS GEOMÉTRICOS - FARIA, TAINARA APARECIDA LOTOSKI (2024)
This study highlights the importance of Mathematics as an intellectual tool and the necessity of adopting innovative approaches in teaching this subject to understand contemporary society. To achieve this goal, we emphasize the importance of moving beyond mere memorization of formulas and rules, promoting contextualized application of mathematical knowledge. In this context, we explore the potential of manipulative materials in teaching, allowing students to experiment, conjecture, and develop hypotheses about mathematical concepts. Recognizing the limitations of these resources, we propose Augmented Reality as a viable alternative. Augmented Reality empowers students to interact with virtual objects that simulate real ones, harnessing the interactivity of technological devices like smartphones. Specifically, our research aimed to analyze the effect of implementing augmented reality resources on learning concepts related to geometry, specifically Platonic solids. Thus, we aimed to examine the effect of implementing augmented reality resources on promoting understanding and exploration of concepts associated with geometric solids, with emphasis on Platonic solids. We conducted a qualitative research with an exploratory and descriptive approach, and participant observation. Our study is based on research related to Augmented Reality and its pedagogical applications, especially regarding its integration into Mathematics education. Additionally, we grounded our study in Vergnaud's Theory of Conceptual Fields, a cognitivism approach based on concepts and cognitive structures. This theory acknowledges that knowledge development is a continuous process dependent on the student's experience and maturity, involving problem-solving and knowledge progression from mental schemas. Data was collected through questionnaires and classroom observations, subjected to Discursive Textual Analysis. Furthermore, we developed the mobile Augmented Reality application “Platonic Solid Viewer” as an educational product of this study, designed to meet users' needs and provide an enriching learning experience. Data analysis revealed that Augmented Reality is an engaging tool for mathematics classes, aiding in the understanding of mathematical concepts, broadening perspectives, and being user-friendly. The study evaluated the didactic potential of the Platonic Solid Viewer application as an Augmented Reality tool in geometry education, especially concerning Platonic solids, through a didactic sequence applied to teachers and students of the 3rd year of high school. The results pointed to the effectiveness of the application in making mathematics classes more engaging and efficient, with students recognizing improvements in understanding Platonic solids through Augmented Reality. Despite identified challenges such as application stability and the availability of suitable devices, the perceived benefits indicate the potential of Augmented Reality to enrich the teaching and learning process in Mathematics.